1999
DOI: 10.2166/wst.1999.0319
|View full text |Cite
|
Sign up to set email alerts
|

Behaviors of nitrifiers in a novel biofilm reactor employing hanging sponge-cubes as attachment site

Abstract: Fluorescence in-situ hybridization (FISH) and DO microelectrodes were applied to biofilms developed in a novel reactor named DHS (downflow hanging sponge-cubes), to investigate the mechanisms of simultaneous carbon removal and nitrification. The DHS reactor was employed as an aerobic post-treatment process after an UASB anaerobic pre-treatment process receiving a municipal sewage. The presence ratio of Nitrosomonas and Nitrobacter cells to total cells of the DHS biomass was estimated by FISH technique to be 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 0 publications
2
34
0
4
Order By: Relevance
“…The profile analysis of the wastewater stream along the height of the G3-DHS bioreactor treating desluging septic tank wastewater showed that soluble COD (organic substance) and ammonia were removed mainly in the upper portion (Figure 2). This finding has also similar presented by other studies [7], [6], [9], [14]. It could be implied that the microenvironment almost certainly differs along the bioreactor height.…”
Section: Performances Of G3-dhs Bioreactorsupporting
confidence: 90%
See 1 more Smart Citation
“…The profile analysis of the wastewater stream along the height of the G3-DHS bioreactor treating desluging septic tank wastewater showed that soluble COD (organic substance) and ammonia were removed mainly in the upper portion (Figure 2). This finding has also similar presented by other studies [7], [6], [9], [14]. It could be implied that the microenvironment almost certainly differs along the bioreactor height.…”
Section: Performances Of G3-dhs Bioreactorsupporting
confidence: 90%
“…The principal objective of this research is to evaluate the performance of the thirdgeneration of downflow hanging sponge (G3-DHS) bioreactor for treatment of desludging wastewater from IPTL. DHS bioreactor was originally published in 1997 by Machdar et al [5] and has been explored for extensive time by numerous researchers [6], [7], [8], [9], [10], [11], [12] for treatment of domestic wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Sedangkan pada bagian atas bioreaktor menunjukkan bahwa sangat efisien dalam menahan padatan dan diikuti biodegradasi oleh bakteri heterotrof. Fenomena ini juga diperoleh oleh peneliti lain (Araki et al, 1999;Machdar et al, 2000;Onodera et al, 2014;Tandukar et al, 2006 …”
Section: Profilunclassified
“…Reaktor DHS telah dikembangkan juga oleh peneliti yang lain di Universitas Teknologi Nagaoka, Jepang sebagai alat pengolahan limbah domestik yang murah dalam biaya operasi terutama untuk negara-negara berkembang sejak tahun 1995 (Machdar et al, 2000). Penelitian bioreaktor DHS awalnya diterbitkan pada tahun 1997 oleh (Machdar et al, 1997) dan telah dieksplorasi terus menerus setiap waktu oleh banyak peneliti (Araki et al, 1999;Machdar et al, 2000;Machdar and Faisall, 2011;Tandukar et al, 2007Tandukar et al, , 2006Tandukar et al, , 2005 untuk pengolahan limbah domestik. Reaktor DHS dapat direkomendasikan sebagai teknologi yang efisien dan hemat biaya untuk pasca pengolahan air limbah kota, terutama untuk negara-negara berkembang seperti penelitian yang telah dilakukan di Mesir (Mahmoud et al, 2011) Sistem reaktor DHS memiliki performa tinggi dalam memproses lumpur aktif yang dicapai dengan stratifikasi mikroba yang berguna untuk mengurangi senyawa organik dan mengoksidasi amonia dan nitrit di dalam reaktor DHS (Kubota et al, 2013).…”
unclassified
“…1995). A variety of tools have been used to study and quantify microbial proliferation, such as light fluorescence (Jones et at 1996), fluorescence in situ hybridization (Araki et al 1999;Davey and O'Toole 2000;'VVimpermy et al 2000), scanning electron microscopy (Brown et a1. 1998), transmission electron microscopy (Sanford et al 1995), X-ray microscopy (Gilbert et a1.…”
Section: Introductionmentioning
confidence: 99%